2006
DOI: 10.3767/000651906x622210
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomic Revision of Hymenophyllaceae

Abstract: SUMMARYA new classification of Hymenophyllaceae, consisting of nine genera (Hymenophyllum, Didymoglossum, Crepidomanes, Polyphlebium, Vandenboschia, Abrodictyum, Trichomanes, Cephalomanes and Callistopteris) is proposed. Every genus, subgenus and section chiefly corresponds to the monophyletic group elucidated in molecular phylogenetic analyses based on chloroplast sequences. Brief descriptions and keys to the higher taxa are given, and their representative members are enumerated, including some new combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
156
0
67

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(227 citation statements)
references
References 42 publications
4
156
0
67
Order By: Relevance
“…cordobense Hieronymus, T. hymenoides Hedwig, T. kraussii Hooker & Greville, T. reptans Swartz and T. tenerum Sprengel. The classification followed here (Morton, 1968) is different from the classification of Hymenophyllaceae suggested by Ebihara et al (2006). Morton (1968) proposed six genera, two of which are the ones treated here.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…cordobense Hieronymus, T. hymenoides Hedwig, T. kraussii Hooker & Greville, T. reptans Swartz and T. tenerum Sprengel. The classification followed here (Morton, 1968) is different from the classification of Hymenophyllaceae suggested by Ebihara et al (2006). Morton (1968) proposed six genera, two of which are the ones treated here.…”
mentioning
confidence: 83%
“…Morton (1968) proposed six genera, two of which are the ones treated here. Ebihara et al (2006) based the classification on molecular phylogenetic analyses using chloroplast sequences and proposed nine genera of (Morbelli, 1980;Tryon & Lugardon, 1991). The spores are variously ornamented and earlier studies of species in the genera Hymenophyllum, Serpyllopsis and Trichomanes from western Patagonia and north-western Argentina by Morbelli (1980Morbelli ( , 1983 have suggested that shape, laesurae form and ornamentation were helpful features for distinguishing taxa at genus level.…”
mentioning
confidence: 99%
“…Las especies se determinaron con base en la obra de Mickel y Smith (2004) y para algunos géneros se consultó literatura reciente (Ebihara, Dubuisson, Iwatsuki, Hennequin, & Ito, 2006;Labiak, 2011). Un ejemplar de cada especie fue montado para su integración en la colección del herbario HGOM del Centro de Investigaciones Biológicas de la Universidad Autónoma del Estado de Hidalgo.…”
Section: Trabajo En Laboratoriounclassified
“…The species were determined based on the work of Mickel and Smith (2004), and for some genera recent literature was consulted (Ebihara, Dubuisson, Iwatsuki, Hennequin, & Ito, 2006;Labiak, 2011). A specimen of each species was mounted for integration into the HGOM herbarium collection, housed in the Biological Research Center at the Universidad Autónoma del Estado de Hidalgo.…”
Section: Laboratory Workmentioning
confidence: 99%
“…As licófitas foram circunscritas de acordo com Kramer & Green (1990) e, para as monilófitas (referidas aqui como samambaias), seguiu-se a circunscrição de famílias proposta por Smith et al (2006), exceto para Cyatheaceae onde seguiu-se Lellinger (1987), e Hymenophyllaceae, para a qual foi adotada a classificação proposta por Ebihara et al (2006). Os táxons compreendidos em cada um desses grupos são citados a partir de família e organizados em ordem alfabética.…”
unclassified